A hit expansion of 3-benzamidopyrazine-2-carboxamide: Toward inhibitors of prolyl-tRNA synthetase with antimycobacterial activity - Pallabothula, Vinod Sukanth Kumar; Abdalrahman, Nechirwan Taimur; Mori, Matteo; Fekri, Amir Hossein; Janďourek, Ondřej; Konečná, Klára; Paterová, Pavla; Novák, Martin; Dudášová-Hatoková, Paulína; Štěrbová-Kovaříková, Petra; Castellano, Carlo; Meneghetti, Fiorella; et al. (Archiv der Pharmazie, 2024)
This study presents an exploration of the chemical space around derivatives of 3-benzamidopyrazine-2-carboxamides, previously identified as potent antimycobacterial compounds with predicted binding to mycobacterial prolyl-transfer RNA synthetase. New urea derivatives (Series-1) were generally inactive, probably due to their preference for cis-trans conformation (confirmed by density functional theory calculations and experimentally by nuclear overhauser effect spectroscopy NMR). Series-2 (3-benzamidopyrazine-2-carboxamides with disubstituted benzene ring) demonstrated that substituents larger than fluorine are not tolerated in the ortho position of the benzene ring. This series brought two new compounds (21: R = 2-F, 4-Cl and 22: R = 2-F, 4-Br) with in vitro activity against Mycobacterium tuberculosis H37Rv as well as multidrug-resistant clinical isolates, with minimum inhibitory concentration ranging from 6.25 to 25 μg/mL. The lactone-type derivatives 4H-pyrazino[2,3-d][1,3]oxazin-4-ones (Series-3) were inactive, but solvent stability studies of compound 29 indicated that they might be developed to usable lactone prodrugs of inhibitors of mycobacterial aspartate decarboxylase (PanD).
Keywords: Antitubercular Agents; pyraziny; molekulární struktura; vztahy mezi strukturou a aktivitou; Molecular Structure; Microbial Sensitivity Tests; vztah mezi dávkou a účinkem léčiva; Pyrazines; Enzyme Inhibitors; Amino Acyl-tRNA Synthetases; antituberkulotika; aminoacyl-tRNA-synthetasy; inhibitory enzymů; Dose-Response Relationship, Drug; Structure-Activity Relationship; mikrobiální testy citlivosti; Mycobacterium tuberculosis